The cluster is not flat: Uneven impacts of brokerage roles on the innovative performance of firms - Luís Martínez-Cháfer; F. Xavier Molina-Morales; Jesús Peiró-Palomino (BRQ Business Research Quarterly, 2018)
This paper investigates whether and to what extent individual firms improve their innovation from behaving as brokers connecting other actors in the Spanish ceramic tile cluster. The effects of the brokerage roles are analyzed for different innovation levels by means of quantile regressions. Finally, we speculate about the indirect and interactive effects of the distinct individual organization attributes and these benefits. Results show that brokerage activities unevenly influence the broker's innovative performance. In addition, the intensity of the impact varies for different innovation levels and the firm's absorptive capacity moderate the final effect of acting as a broker."
Keywords: 650; Broker; Industrial cluster; Innovation; Social network analysis; Quantile regression; Ceramic industry